STRUKTUR DAN FUNGSI MITOS KERAJAAN RAJA AMPAT - Malawat, Insum (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2017)
Myth as a research object can be studied from different angles. Quantity of study greatly determines the quality of the story. The concrete form of learning folklore is done by reusing the hidden values in it to see its relevance to contemporary life. Various means of literature used in a story is in order to function mengkistalkan meaning or message to be conveyed. This shows the urgency and significance of a cultural symbol in the mythical text as the entityâs identity.This paper applies to the structure and function of the Maya mythology of Raja Ampat Regency full of Raja Ampat Kingdom Myth (MKRA). The depiction of the story structure is structured according to elements of Lucian Goldmannâs worldview. Meanwhile, the description of Bastian and Mitchelâs functions and culture through a pragmatic approach.